PELAKSANAAN EVALUASI KURIKULUM DI MTs AL-JIHAD - Hadi Widodo; Zamzami Zamzami (Jurnal Al-Fatih, 2020)
Curriculum evaluation is a systematic effort to collect information about a curriculum to be implemented as a “material” for consideration of the value and meaning of the curriculum in a particular context. In fact, curriculum evaluation includes the entire curriculum or each curriculum component, including the objectives, content and learning methods. This paper examines the implementation of curriculum evaluation at MTs Al-Jihad. The focus of the discussion is oriented towards the aspect of curriculum evaluation as part of the management system, evaluation of madrasah performance, and evaluation of the state of students in the last 3 years. This study uses a qualitative approach with a literature study method. As for the results of this study indicate that (1) implementation of curriculum evaluation is a form of final measurement and assessment in an implementative cycle of educational activities, the review is focused on planning, implementation, monitoring and assessment; (2) achievements as part of the existence of the institution in demonstrating the progress of the educational process have been achieved well by MTs Al-Jihad, this is evidenced by 4 regional achievements in 2019, 2 achievements at the District / City level in 2018, 1 achievement at the District / City level. in 2017, and 1 achievement at the district / city level in 2016; (3) aspects of the condition of students in the last 3 years (2017/2018, 2018/2019, 2019/2020) have always increased, even in the 2020/2021 school year before registration was opened, 35 registrants were recorded. Thus, this evaluative review shows that there has been an increase in the quality of institutions in a comprehensive manner at MTs Al-Jihad.